2016
DOI: 10.2305/iucn.ch.2016.parks-22-1bps.en
|View full text |Cite
|
Sign up to set email alerts
|

Indicators for assessing good governance of protected areas: Insights from park managers in Western Australia

Abstract: Effective management of protected areas relies on good governance. An assessment was undertaken using the standards provided by the United Nations Development Programme's characteristics of good governance for sustainable development as a starting point. Being able to assess governance based on indicators is essential for ongoing effective management through improving practice. Although indicators and evaluation frameworks are available, they do not offer protected area managers a quick, comprehensive measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Abrams et al (2003) and Borrini-Feyerabend et al (2013) provided more than 100 such indicators, associated with five of the good governance principles of Graham et al (2003) (Table 2.1). Shields et al (2016) have identified a significantly smaller number of broadly useful indicators (20) based on a three-round Delphi survey with the Australian PA managers and experts. Along with that, instead of the nine original UNDP governance principles (Table 2.1), the authors employed 10, by splitting the 'efficiency and effectiveness' principle into 'efficiency' and 'effectiveness' as separate requirements.…”
Section: Understanding the Concept Of Pa Governance And Its Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Abrams et al (2003) and Borrini-Feyerabend et al (2013) provided more than 100 such indicators, associated with five of the good governance principles of Graham et al (2003) (Table 2.1). Shields et al (2016) have identified a significantly smaller number of broadly useful indicators (20) based on a three-round Delphi survey with the Australian PA managers and experts. Along with that, instead of the nine original UNDP governance principles (Table 2.1), the authors employed 10, by splitting the 'efficiency and effectiveness' principle into 'efficiency' and 'effectiveness' as separate requirements.…”
Section: Understanding the Concept Of Pa Governance And Its Assessmentmentioning
confidence: 99%
“…By using the DPSIR framework, 5 Eklund and Cabezza (2017) tried to explain how governance quality affects specific PA management outcomes. Based on a three-round Delphi survey involving 33 middle-to seniorlevel staff from Western Australian PA agencies, Shields et al (2016) identified 20 good governance indicators in the form of questions (aligned with ten governance principles). The authors connected them with the accompanying output measures, e.g.…”
Section: Relationship Between the Pa's Governance And Management Effectiveness Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lockwood provides one of the few published efforts to integrate evaluation of protected area governance with PAME evaluations placing good governance principles 'above' the evaluation components of context, planning, inputs, process, outputs, and outcomes (Shields et al, 2016).…”
Section: Evaluating Protected Area Governancementioning
confidence: 99%
“…Most efforts to assess social equity in PAs have focused on identifying the distribution of costs and the sharing of benefits (for a review see Schreckenberg et al 2010 andde Lange et al 2016). Procedural issues and their links with matters of recognition have received less attention (see Lockwood 2010;Borrini-Feyerabend et al 2013;Wilkie et al 2015;Shields et al 2016). Furthermore, although multidimensional social equity principles in PAs have been conceptually defined (Schreckenberg et al 2016), still the variety of methodologies and tools employed to assess the different dimensions of social equity separately (see de Lange et al 2016 for a review), along with budget and time constraints, are key concerns for policy makers and specially those working on conservation practice.…”
mentioning
confidence: 99%